Shyness and academic procrastination among Chinese adolescents: a moderated mediation model of self-regulation and self-focused attention - Sun, Hong; Yu, Yang; Peng, Chao (Frontiers in Psychology, 2024)
Academic procrastination is a common concern among adolescents，but the correlation between shyness and academic procrastination and the internal mechanisms have not yet been thoroughly investigated. Based on a questionnaire survey with 1279 Chinese middle school students, this study examined the effect of shyness on academic procrastination and its underlying mechanism of selfregulation and self-focused attention. Results revealed that: (1) Shyness significantly predicted academic procrastination. (2) Self-regulation mediated the relationship between shyness and academic procrastination. (3) Self-focused attention played a moderating role in the first half of this mediation process. Specifically, higher level of self-focused attention strengthened the predictive effect of shyness on self-regulation. These results underscored the latent risks and protective factors associated with shyness, self-regulation, and self-focused attention in adolescent academic procrastination. In future research and interventions, attention may be directed towards improving individual internal factors to assist adolescents in effectively addressing issues related to academic procrastination.